Concept Analysis of Occupational Therapy Handling in the Children with Cerebral Palsy: A Hybrid Model - Hamid Dalvand; Mehdi Rassafiani; Seyyed Ali Hosseini; Seyyed Ali Samadi; Hamid Reza Khankeh (University of Social Welfare and Rehabilitation Sciences, 2015)
Objective: This study aimed to analyze the concept of occupational therapy handling in the children with cerebral palsy from the perspective of occupational therapy instructors and clinicians in Iran. Materials & Methods: In this qualitative study, using hybrid model to clarify the concept of handling through three phases. For the theoretical phase, attributes of handling were recognized through a review of the literature (until February 2014), and six in-depth semi - structured interviews, two observations and one panel of experts were conducted for the fieldwork to develop attributes from the data and to verify those identified from the literature review. In the third phase attributes and final analysis of handling were extracted from the first and second phase. Results: The results were classified in five main categories that were identified as: (1) care of child, (2) management of treatment, (3) manual techniques, (4) education of activities of daily living (ADL), and (5) lifting and carrying. Core attributes of handling include "control, safety, transfer and positioning". Conclusion: It seems that the results of this study may help in clarifying the concept of handling in children with CP. In addition, by identifying the process, barriers and facilitative factors, and the concept of handling, occupational therapy instructors and therapists will be able to design and run their educational activities based on scientific findings which can provide them with the necessary conditions for education, learning and proper execution of handling in occupational therapy.